The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12871-019-0837-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endotracheal tube lubrication on cuff pressure increase during nitrous oxide exposure: a laboratory and prospective randomized controlled trial

Abstract: Background We previously demonstrated that lubrication of an endotracheal tube (ETT) cuff with K-Y™ jelly strongly and significantly inhibited the increase in cuff pressure during nitrous oxide (N 2 O) exposure in vitro. However, in our previous study, we identified critical differences between some influential factors, such as the amount of lubricant retained on the cuff, and studied temperature differences between laboratory and clinical conditions. Therefore, it remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…It has been reported that tube lubrication with K-Y jelly (Johnson & Johnson, USA) inhibits the increase in cuff pressure in vitro when using a tube with a cuff under general anesthesia using N2O. However, its clinical significance is limited [67]. The advantage of using an uncuffed tube in children is that a tube with a larger internal diameter can be used, thereby reducing airway resistance and work of breathing.…”
Section: Nasotracheal Intubation In Pediatric Patientsmentioning
confidence: 99%
“…It has been reported that tube lubrication with K-Y jelly (Johnson & Johnson, USA) inhibits the increase in cuff pressure in vitro when using a tube with a cuff under general anesthesia using N2O. However, its clinical significance is limited [67]. The advantage of using an uncuffed tube in children is that a tube with a larger internal diameter can be used, thereby reducing airway resistance and work of breathing.…”
Section: Nasotracheal Intubation In Pediatric Patientsmentioning
confidence: 99%
“…Fraglich war der Einfluss der inneren Körpertemperatur auf den Druckanstieg im Cuff. Studien haben gezeigt, dass Lachgas schneller zu einem Volumen-und Druckanstieg in gasgefüllten Räumen führt, je niedriger die Temperatur ist [41,42]. Die Temperaturunterschiede sind in unserer Studie im Vergleich zu den in-vitro-Studien jedoch sehr gering, sodass ein Einfluss auf den Cuffdruck unwahrscheinlich ist und in unserem Versuchsansatz nicht detektierbar war.…”
Section: Introductionunclassified